'Let this forest for ever rest':* tracking protest and identity in Australia's forests. Issue 3 (3rd July 2019) - O'Brien, Thomas
ABSTRACT: Exploitation of natural resources has long been a flashpoint for contention in Australia. This is clear in the case of forest management, where groups advocating protection have faced off against state and industry actors. The move towards multifunctionalism that recognises different values in the management of natural resources has led to a search for alternative solutions. In the case of forestry, introduction of Regional Forest Agreements (RFA) in the 1990s sought to devolve responsibility to the States, while striking a balance between economic and environmental considerations. The aim of this paper is to identify how forest activism has developed since the RFA process began and its significance in relation to changes in land use. The paper draws on a protest event catalogue of forest-related events over the 1997–2017 period to identify the intensity, tactics and location of such actions. The findings suggest that state action has reduced the intensity of contention, in line with changes in resource management practices. However, they also point to the importance of identity and its link to the social construction of resources in determining the ability of actors to de-escalate and find solutions.